Virus-Mediated Metalloproteinase 1 Induction Revealed by Transcriptome Profiling of Bovine Herpesvirus 4-Infected Bovine Endometrial Stromal Cells. Issue 1 (1st July 2016) - Tebaldi, Giulia; Jacca, Sarah; Montanini, Barbara; Capra, Emanuele; Rosamilia, Alfonso; Sala, Arianna; Stella, Alessandra; Castiglioni, Bianca; Ottonello, Simone; Donofrio, Gaetano
Abstract: Viral infections can cause genital tract disorders (including abortion) in cows, and bovine herpesvirus 4 (BoHV-4) is often present in endometritis-affected animals. A major problem with cattle uterine viral infections in general, and BoHV-4 in particular, is our limited understanding of the pathogenic role(s) that these infections play in the endometrium. A similar lack of knowledge holds for the molecular mechanisms utilized, and the host cell pathways affected, by BoHV-4. To begin to fill these gaps, we set up optimized conditions for BoHV-4 infection of a pure population of bovine endometrial stromal cells (BESCs) to be used as source material for RNA sequencing-based transcriptome profiling. Many genes were found to be upregulated (417) or downregulated (181) after BoHV-4 infection. As revealed by enrichment functional analysis on differentially expressed genes, BoHV-4 infection affects various pathways related to cell proliferation and cell surface integrity, at least three of which were centered on upregulation of matrix metalloproteinase 1 ( MMP1 ) and interleukin 8 ( IL8 ). This was confirmed by reverse transcription PCR, real-time PCR, Western-immunoblot analysis, and a luciferase assay with a bovine MMP1-specific promoter reporter construct. Further, it was found that MMP1 transcription was upregulated by the BoHV-4 transactivator IE2 /RTA, leading to abnormally high metalloproteinase tissue levels, potentially leading to defective endometrium healing and unresolved inflammation. Based on these findings, we propose a new model for BoHV-4 action centered on IE2-mediated MMP1 upregulation and novel therapeutic interventions based on IFN gamma-mediated MMP1 downregulation.